Assessment of Blood-Brain Barrier Permeability in a Cerebral Ischemia-Reperfusion Model in Rats; A Pilot Study - Kozler, P; Marešová, D; Pokorný, J (Physiological research, 2024)
Animal models are an important tool for studying ischemic mechanisms of stroke. Among them, the middle cerebral artery occlusion (MCAO) model via the intraluminal suture method in rodents is closest to human ischemic stroke. It is a model of transient occlusion followed by reperfusion, thus representing cerebral ischemia-reperfusion model that simulates patients with vascular occlusion and timely recanalization. Although reperfusion is very beneficial for the possibility of preserving brain functions after ischemia, it also brings a great risk in the form of brain edema, which can cause the development of intracranial hypertension, and increasing morbidity and mortality. In this paper, we present the results of our own transient reperfusion model of MCAO in which we tested the permeability of the blood-brain barrier (BBB) using Evans blue (EB), an intravital dye with a high molecular weight (68,500 Da) that prevents its penetration through the intact BBB. A total of 15 animals were used in the experiment and underwent the following procedures: insertion of the MCA occluder; assessment of ischemia by 2,3,5 -Triphenyltetrazolium chloride (TTC) staining; assessment of the BBB permeability using brain EB distribution. The results are presented and discussed. The test of BBB permeability using EB showed that 120 minutes after induction of ischemia, the BBB is open for the entry of large molecules into the brain. We intend to use this finding to time the application of neuroprotective agents via ICA injection in our next stroke model. Keywords: Cerebral ischemia-reperfusion model, Middle cerebral artery occlusion, Blood-brain barrier, 2,3,5 -Triphenyltetrazolium chloride, Evans blue.
Keywords: ischemie mozku; Brain Ischemia; permeabilita; kapilární permeabilita; hematoencefalická bariéra; Permeability; Blood-Brain Barrier; reperfuzní poškození; krysa rodu Rattus; zvířata; Capillary Permeability; potkani Wistar; pilotní projekty; Pilot Projects; potkani Sprague-Dawley; Rats, Wistar; Male; infarkt arteria cerebri media; Infarction, Middle Cerebral Artery; Reperfusion Injury; Rats; Rats, Sprague-Dawley; Animals; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech